Mekanisme Pelaporan Pajak Penghasilan 21 Melalui Coretax Administration System Pada BPKAD Kabupaten Jember - Maulina Putri Abdillah (Fakultas Ilmu Sosial dan Ilmu Politik, 2026)
The modernization of Indonesia tax administration through the Coretax Administration System marks a fundamental transformation in tax obligation management within regional government agencies. The Regional Financial and Asset Management Agency (BPKAD) of Jember Regency, acting as a withholding agent, is obligated to calculate, deduct, remit, and report Article 21 Income Tax (PPh 21) on civil servant 2019 (ASN) salaries using the Average Effective Rate (TER) scheme pursuant to Minister of Finance Regulation Number 168 of 2023. This final project aims to analyze the mechanism for reporting PPh Article 21 on ASN salaries through the Coretax Administration System at BPKAD Jember Regency. The field work practice was conducted over 40 working days at BPKAD Jember Regency using direct observation, interviews with the Expenditure Treasurer, and documentary research on applicable tax regulations. Data collected encompassed qualitative data on reporting procedures and technical challenges, as well as quantitative data comprising PPh 21 calculations for employees under TER Categories A, B, and C. The findings reveal that the PPh 21 reporting mechanism at BPKAD Jember Regency operates systematically through six stages: salary document preparation, login and access to the Coretax system, taxpayer data entry and TER category assignment, automated tax calculation and deduction, payment remittance via billing code, and electronic submission of the Monthly PPh 21 Tax Return. The TER scheme within Coretax successfully automates tax calculation based on gross income and employee PTKP status, while simultaneously generating electronic withholding tax certificates (Form 1721-A2). The entire mechanism complies with PMK Number 168 of 2023.
:: Finalisasi file repositori 22 Juli 2026_Kurnadi
Keywords: pph21; coretax admnistration system; Bendahara Instansi; ASN